BASES OF THEORETIZATION AND QUALITY MANAGEMENT OF FORMATION OF PROFESSIONAL AND TECHNICAL CULTURE OF A CONSTRUCTION ENGINEER - E. Aleshina; I. Butsuk; I. Spiridonova (Вестник Северо-Кавказского федерального университета, 2022)
The article highlights the problems of theorization and quality management of the formation of the professional and technical culture of a civil engineer. The concepts of «quality management principles for the formation of a professional and technical culture of a civil engineer», «quality managementfunctions for the formation of a professional and technical culture of a civil engineer», «quality management models for the formation of a professional and technical culture of a civil engineer», «quality management technology the formation of the professional and technical culture of the civil engineer», «pedagogical conditions for effective quality management of the formation of the professional and technical culture of the civil engineer». The prospects for theorization and quality management of the formation of the professional and technical culture of a civil engineer in the context of modern continuous education are determined.